Biochemical parameters and nutritional status of surgical patients with gastrointestinal cancer: a literature review - DANIELA CARLA ALBERTI; ROSANA AMORA ASCARI; EMANUELA MEDEIROS SCHIRMER (Revista do Colégio Brasileiro de Cirurgiões, 2020)
ABSTRACT This is an integrative literature review with the objective of identifying the relationship between biochemical parameters and the nutritional status of surgical patients with cancer of the gastrointestinal tract, developed in April 2019, encompassing the databases SCOPUS (Elsevier), PubMed Central® (PMC), and the Cochrane Virtual Health Library (BVS). We used the terms “Gastrointestinal Neoplasm” AND “Nutritional Status” AND “Blood Chemical Analysis” with the aid of the Academical software after the protocol validation. Out of 147 articles analyzed, seven were included in the review, as they met the inclusion criteria. There were relevant associations between biochemical parameters and nutritional status. Impaired nutritional status can negatively influence the postoperative outcome. The monitoring of interdisciplinary teams can assist in the recovery of these patients and prevent unfavorable outcomes.